Choosing the right public transport solution based on performance of components - Bruun, Eric; Allen, Duncan; Givoni, Moshe (Transport, 2018)
Planners often focus on a specific mode too early in the design and selection process, especially on the choice between bus and rail technology. It may be that available Right of Way (RoW), alignment characteristics and other design features are more important. In this paper, we first identify the principal components central to performance of a particular role common to all major Public Transport (PT) investments. The primary aim is to offer a more mode-neutral alternative selection process that benefits from ex-post cost and performance information about a substantial number of actual PT systems broken down into these components to the extent that is possible. Less quantitative components and features, such as passenger experience, scalability, and implementability are then discussed for their role in increasing or diminishing the attractiveness of alternative candidate component packages in the desired range of the quantitative criteria. The results show that investment costs increase with the degree of separation of RoW, regardless of rail or bus technology, with rail having an additive “technology premium”. Higher Average Operating Speed (AOS) reduces investment in vehicles and the Operating and Maintenance (O&M) cost, regardless of technology. At low/moderate passenger traffic densities, Semirapid Bus modes have lower O&M costs than Semirapid Rail. At the highest densities, Rapid Rail and Regional Rail modes exhibit clear economies of scale. For mixed street running, rail-related components cause a far more expensive total investment on per unit of Productive Capacity (PC) basis. As the required PC increases, rail modes become consistently less expensive. The main conclusion is that in order to improve value-for-money of PT it is critical to develop innovative component technologies and construction techniques, which are not necessarily rail or bus specific.